Externalities on Waste Management in Kampung Tempe Surabaya from Islamic Perspective - Qudsi Fauzi, R. Moh.; Rimadiyanti, Fitria; Cahyono, Eko Fajar (International Journal of Psychosocial Rehabilitation, 2020)
This study examines how the externalities of tempe’s industrial waste management in Kampung Tempe Surabaya are reviewed from Economics of Natural Resources and Environment in Islamic Perspective. This research is conducted by using qualitative approach with case study method. Data collection conducted in this study by in-depth interviews and direct observation to the object of research. Technical analysis used in this research is by data reduction, data presentation, as well as withdrawal conclusions and verification from in-depth interviews and direct observation. The results show that there are externalities of tempe’s industrial waste management in Kampung Tempe Surabaya which is indicated by absence of unpleasant odor from waste, makes environment of Kampung Tempe more cleaner, provide jobs, increase incomes, and get a facilities and infrastructure.